Resistance Against the Soviet Regime in the Seventies and Eighties in Lithuania - Račkauskaitė, Živilė (Genocidas ir rezistencija, 1999)
Different underground organizations united in the 1970s, forming a national opposition and focusing on the survival of Lithuania. At the end of the 1980s, it became a national movement with its underground publications and an organisation united by the ideas of nationalism. The major publications of the movement were Aušra, Vytis and Laisvės in particular, reflects that the ultimate end of the originaters of publications was free Lithuania eighties, the movement can relatively be streamed into three major oppositions: the Lithuanian Catholic Church opposition (LCC), radical-nationalist, and liberal-nationalist oppositions. The LCC movement focused on the violation of the freedom of religious believes in Lithuania whereas the priorities, although the issue has always been spoken euphemistically.